Sexual attraction and childhood association a Chinese brief for Edward Westermarck - Wolf, Arthur P. 1932-2015 (Stanford Univ. Press, 1995)
Freud's challenge carried the day and became the standard view throughout the social and biological sciences. Consequently, the question was: why do all societies repress this natural inclination? Biologists argued that the incest taboo protected us from dangers of inbreeding; sociologists argued that it was necessary to prevent sexual rivalry that would destroy the family; and anthropologists saw the real purpose of the taboo as forcing families to exchange women in marriage